Identification of benzo[c]phenanthridine metabolites in human hepatocytes by liquid chromatography with electrospray ion-trap and quadrupole time-of-flight mass spectrometry - Kosina, Pavel; Vacek, Jan; Papoušková, Barbora; Stiborová, Marie; Stýskala, Jakub; Cankař, Petr; Vrublová, Eva; Vostálová, Jitka; Simánek, Vilím; Ulrichová, Jitka (Journal of chromatography. B, Analytical technologies in the biomedical and life sciences, 2011)
The metabolism of the benzo[c]phenanthridine alkaloids was studied using human hepatocytes which are an excellent model system for biotransformation studies. For analysis of the alkaloids and their metabolites, an electrospray quadrupole ion-trap mass spectrometry (ESI ion-trap MS) connected to a reversed phase chromatographic system based on cyanopropyl modified silica was used. The optimized experimental protocol allowed simultaneous analysis of the alkaloids and their metabolites and enabled study of their uptake into and interconversion in human hepatocytes. The results show that formation of the dihydro metabolite which may be followed by specific O-demethylenation/O-demethylation processes, is probably the main route of biotransformation (detoxification) of the benzo[c]phenanthridines in human hepatocytes. The structure of the main O-demethyl metabolite (2-methoxy-12-methyl-12,13-dihydro-[1,3]dioxolo[4',5':4,5]benzo[1,2-c]phenanthridin-1-ol; 336.1 m/z,) was proposed by the multi-stage MS and quadrupole time-of-flight MS methods using chemically synthesized standard.
Keywords: kultivované buňky; Aged; Cells, Cultured; Tandem Mass Spectrometry; vysokoúčinná kapalinová chromatografie; lidé středního věku; oxidace-redukce; senioři; tandemová hmotnostní spektrometrie; Hepatocytes; Isoquinolines; biotransformace; lidé; benzofenantridiny; Adult; Reproducibility of Results; Middle Aged; dospělí; isochinoliny; reprodukovatelnost výsledků; hepatocyty; Female; Biotransformation; Oxidation-Reduction; Male; ženské pohlaví; hmotnostní spektrometrie s elektrosprejovou ionizací; Humans; mužské pohlaví; Benzophenanthridines; Chromatography, High Pressure Liquid; Spectrometry, Mass, Electrospray Ionization